Thermoplastic composite pipe failure envelopes under axisymmetric and thermomechanical loading. (1st March 2023) - He, Yangye; Augusto Vaz, Murilo; Caire, Marcelo
Abstract: Thermoplastic composite pipes are considered to be the next riser design generation for deep and ultra-deep water offshore oil field development. They typically consist of polymeric (e.g. PEEK or PVDF for high temperature applications) and composite laminate (e.g. carbon/glass fibers) layers. Theoretical and finite element (FE) analyses of thermoplastic composite pipes under axisymmetric loadings with thermal gradient due to internal surface temperature and external convection to the seawater are presented in this work. The pipe consists of an inner and outer isotropic homogeneous polymeric layers and intermediate transversely isotropic perfectly bonded laminate ply layers. The through-thickness failure indexes related to the von Mises and Maximum Stress criteria are respectively evaluated for polymer and laminate layers. The pipe is assumed to fail when one of the failure indexes across the pipe thickness reaches 1. In the case study, the pipe through-thickness temperature profiles and stress states obtained from analytical and FE models agree well. The linearity response behavior of thermoplastic composite pipe under isolated mechanical and thermal loadings is investigated. Based on the failure analyses, the pipe maximum load envelopes under axisymmetric loading condition and the related failure layer illustration are given. The pipe axial stiffness is invariable regardless of the internal and external pressures, but slightly decreases as the prescribed temperature increases.